The logos Christology in the fourth gospel (Jn 1:1–5, 14): A soteriological response to an Ewe cosmic prayer - Sakitey, Daniel; van Eck, Ernest (Hervormde teologiese studies, 2023)
This article interprets the logos Christology in the fourth gospel within Ewe-Ghanaian cosmic setting. The article employs a combination of the exegetical and mother tongue biblical hermeneutics as its methodologies. The article compares the concept of the logos in John 1:1–5, 14 with a similar concept in Ewe cosmology with the aim of finding their points of convergence and divergence. The article also identifies linguistic and theological gaps in the Ewe rendition of John 1:1–5, 14 and proposes a new translation that addresses it. A translation of the logos in Ewe cosmic perspective renders the term nyagbe, the intelligible word which dwells with the female pair of Sogbe-Lisa and manifests itself from the absolute state of existence [ logo ] to the embodied state [ logosu ]. When nyagbe journeyed from the eternal state of existence to the embodied state of existence, it manifests itself at five different levels of existence until it reaches the final state where humans exist. Although believed to be the epitome of all creation, human beings are at the same time described as being at the shore of ignorance and therefore must continually climb the ladder of knowledge in order to free themselves from it. It is for this reason that humans constantly petition the cosmic forces for their salvation. The article therefore, identifies a soteriological gap created in the Ewe soteriology and concludes that the only soteriological response to the Ewe cosmic cry for deliverance from the state of ignorance is the logos incarnate in John 1:14. Contribution: The article contributes to the academic knowledge on the logos Christology in the prologue of the fourth gospel (John 1:1–5, 14), specifically in the use of mother tongue in biblical hermeneutics in Africa.